The Buddhist Decision - Making Model for School Administrators under the Secondary Educational Service Area Office 1, Bangkok - คำน้อย พระครูปลัดไกรสอน ธมฺมรสี; งามประโคน สิน; ศรีวิชัย สุทธิพงษ์; แหวนเพชร วิชัย (Journal of Educational Review Faculty of Education in MCU, 2018)
The objectives of this research were; 1) to study the current situations and problems of decision making of school administrators under the Secondary Educational Service Area Office 1, Bangkok, 2) to develop a Buddhist decision model for school administrators, and 3) to propose a model of Buddhist decision making for school administrators. The mixed research methodology was used in the study. The quantitative data were collected from 261 subjects by questionnaires and analyzed by frequency, percentage, mean, and standard deviation. The qualitative data were obtained from in-depth interviews with 9 key-informants and group discussions with 9 experts, and then analyzed by content analysis. The research results found that: 1. The current situations and problems on decision making of school administrators under the Secondary Educational Service Area Office 1, Bangkok, in personnel administration, academic administration, general administration, and budget administration were at the high level overall. The current problems concerning decision making consisted of unskillful teachers, personnel recruitment, budget shortage for training and seminar, continuing personnel development, work monitor and supervision, teaching and activities in schools, personnel training, and lack of best practice training in human resource management. In general administration, work improvement should be done in security, maintenance, building using, public relations and support education in accordance with policy. 2. In the development of a Buddhist decision making model for school administrators under the Secondary Educational Service Area Office 1, Bangkok, the principles of the Four Noble Truths and Critical Reflection should be integrated in academic, budget, personnel and general administration relating to 7 steps of decision making theory of Plunkett and Attner; problem identification, factors limitation identification, alternative development, alternative analysis, optimal solution identification, implementation, and creating a control and evaluation system. 3. The Buddhist decision making model in application with Plunkett and Attner’s 7-step model relevant to the Four Noble Truths integrated with Critical Reflection results to the "DDM Model" for school administrators in the most effective making decision in academic administration, budget administration, personnel administration and general administration.